2020
DOI: 10.15517/rbt.v68i4.40805
|View full text |Cite
|
Sign up to set email alerts
|

Early life history of the Caribbean coral Orbicella faveolata (Scleractinia: Merulinidae)

Abstract: Abstract. Introduction: Rehabilitation of hermatypic coral species that have declined in the Caribbean in recent decades is a priority. Production of sexual recruits is considered the best restoration method to aid affected populations. Objective: To gain knowledge of early life stages of Orbicella faveolata and to enhance production of new sexual recruits. Methods: Gamete bundles from the coral species O. faveolata were collected over three years (2016, 2018, and 2019) from Los Corales del Rosario y de San Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
1
0
0
Order By: Relevance
“…Thus, results from this study showed that within the rst 7 days after reaching competence to settle, average mortality is two-four-fold higher compared to the percentage of settlement, further suggesting this period is a bottleneck of survivorship for D. labyrinthiformis. Other studies conducted for Caribbean (Rylaarsdam 1983;Vermeij and Sandin 2008;Alvarado-Chacon et al 2020) and Indo Paci c corals show similar results (Babcock 1985;Babcock and Mundy 1996;Babcock et al 2003;Wilson and Harrison 2005). Thus, our results are consistent with the nding that high mortality rates during the initial stages of their life cycle are a critical part of life-history traits in corals (Trapon et al 2013).…”
Section: Resultssupporting
confidence: 92%
“…Thus, results from this study showed that within the rst 7 days after reaching competence to settle, average mortality is two-four-fold higher compared to the percentage of settlement, further suggesting this period is a bottleneck of survivorship for D. labyrinthiformis. Other studies conducted for Caribbean (Rylaarsdam 1983;Vermeij and Sandin 2008;Alvarado-Chacon et al 2020) and Indo Paci c corals show similar results (Babcock 1985;Babcock and Mundy 1996;Babcock et al 2003;Wilson and Harrison 2005). Thus, our results are consistent with the nding that high mortality rates during the initial stages of their life cycle are a critical part of life-history traits in corals (Trapon et al 2013).…”
Section: Resultssupporting
confidence: 92%
“…Thus, results from this study showed that within the rst 7 days after reaching competence to settle, average mortality is two-four-fold higher compared to the percentage of settlement, further suggesting this period is a bottleneck of survivorship for D. labyrinthiformis. Other studies conducted for Caribbean (Rylaarsdam 1983;Vermeij and Sandin 2008;Alvarado-Chacon et al 2020) and Indo Paci c corals show similar results (Babcock 1985;Babcock and Mundy 1996;Babcock et al 2003;Wilson and Harrison 2005). Thus, our results are consistent with the nding that high mortality rates during the initial stages of their life cycle are a critical part of life-history traits in corals (Trapon et al 2013).…”
Section: Resultssupporting
confidence: 91%
“…This study was conducted at the inner-shelf reef Enrique (17°57.15′ N, 67°02.55′ W) and the mid-shelf reef San Cristobal (17°56.30′ N, 67°04.45′ W) in La Parguera Puerto Rico ( Figure 1 ). Twelve colonies of O. faveolata were collected by SCUBA divers at depths ranging from 1 to 3 m, ensuring a 3 m distance between sampling locations to minimize sampling genetic clones [ 15 , 16 , 17 ]. The colonies were tagged by inserting a nail into the substrate near the colony and attaching a plastic tag with a unique identification number to the stainless steel nail.…”
Section: Methodsmentioning
confidence: 99%